Relocalizing the judicial space: Place, access and mobilization in judicial practice in post-crisis Argentina - Barrera Lopez, Leticia (2012)
This article presents an image of the judicial space that seeks to challenge ubiquitous representations and scholarly metaphors of legal settings that recreate judicial practice as constrained within a delimited site. The article draws on ethnographic work conducted at the Argentine Supreme Court between August 2005 and March 2007, and focuses on the direct observation of the Argentine Supreme Court's daily dynamic articulated by concrete senses of mobility and access. Additionally, it builds upon the aesthetics of restoration, prompted by the scene of the restoration of the Court's building, to suggest the tensions that arise out of the efforts to reconstruct the judicial order in post 2001-2-crisis Argentina, constantly disrupted by the institution's own routine.